SATISFACTION AND WILLINGNESS TO PAY PHARMACISTS COUNSELING SERVICES IN SURAKARTA - Mariska Sri Harlianti; Khusnul Novitasari (Jurnal Farmasi Sains dan Praktis, 2020)
Satisfaction was an indicator to assess the quality of counseling services by pharmacists in pharmacies. Willingness to Pay (WTP) was an approach that can be used to measure the indirect benefits of a program. Satisfaction and WTP have a positive correlation. The increasing level of consumer satisfaction caused an increase in the value of WTP. The purpose of this study was to measure the satisfaction and WTP value of counseling services by pharmacists and the relationship between them. Non-experimental research with cross sectional design was conducted on 100 patients who visited the pharmacy and received counseling services by the pharmacist. Satisfaction was measured based on 4 dimensions, namely: tangible, reliability, assurance, and empathy. WTP value was determined using the payment card method. The relationship between the two variables was analyzed by the Pearson correlation (p-value <0.05). The results showed that the level of satisfaction and WTP of counseling services by pharmacists in the Surakarta city pharmacy was 0.93 and Rp 20,652 and there was no relationship between them (Sig. = 0.422). The high level of satisfaction showed that the quality of service was also good. However, it did not affect respondents to pay for counseling services by pharmacists in the Surakarta city area pharmacy with a relatively higher value when compared to other professions